Tinjauan Pustaka Pada Analisis Pushover Terhadap Kekakuan Struktur Portal Beton Bertulang Dengan Dinding Bata - Salsabila, Elsa Attila; Ridwan, Ridwan (Dept. of Civil Engineering Universitas Riau, 2023)
This research evaluates the impact of adding masonry walls on the stiffness and stability of building structures, focusing on pushover analysis and seismic behavior through a review of several journals. According to the research conducted by Hutajulu et al. (2019), masonry walls serve as significant structural elements rather than mere non-structural components. Through numerical analysis of the curves in the study, it was found that structures with masonry walls have a higher peak stiffness of 27.362 kN/mm, capable of withstanding a maximum load of 7490.93 kg with a displacement of 15.058 mm, compared to portals without walls, which only achieve a peak stiffness of 10.386 kN/mm and can withstand only 1451.91 kg. The stiffness difference between both portals reaches 66.242%. Similar studies by Majumder et al. (2017) and Mukhlis et al. (2022) also yielded comparable results, indicating that structures or portals accounting for the addition of walls exhibit significantly greater stiffness compared to those without walls, with stiffness differences exceeding 50%. In addition to its effect on stiffness, the addition of masonry walls also impacts the base shear capacity that the portal or structure can bear, as the inclusion of walls allows for greater lateral forces to be resisted compared to conditions without walls. For instance, in Hutajulu et al.'s (2019) study, the base shear for bare frames was only 14.025 kN, while infilled frames reached as high as 74.918 kN. These findings demonstrate that incorporating masonry walls into structures or portals enhances their resistance to lateral loads compared to those without masonry walls, contributing additional strength, stiffness, and earthquake resilience to the structure. Therefore, masonry walls should be treated as integral structural elements in building design to ensure safety and optimal performance under various load conditions.